Senam Hamil Dalam Upaya Penurunan Nyeri Punggung Pada Ibu Hamil Trimester III Di Posyandu Kampung Tri Tunggal Jaya, Kec. Gunung Agung, Kab. Tulang Bawang Barat, Lampung - Riona Sanjaya; Atik Yuli Nariyati; Ayu Rofika; Linda Sari; Nita Kurniasari; Meliana Meliana; Ica Fitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Due to the fetus's expansion in the uterus, the mother's pelvic joints are slightly more mobile, resulting in back pain. Additionally, the shoulders are pulled back and the lumbar spine is more curved, both of which increase spinal joint flexibility. To overcome back pain, one effort that can be done is pregnancy exercise. The goal of this volunteer project is to develop a unified strategy for preventing and treating pregnancy-related back pain by educating the public about the issue. Implementation in community service activities on October 3, 2023 at 09:00 - 12:00 WIB has been followed by pregnant women totaling 10 pregnant women, with the average results of knowledge before counseling amounting to 52.5 and after counseling amounting to 89.0 it is concluded that overall counseling participants with good knowledge. It is hoped that by raising awareness of pregnancy exercises, particularly among pregnant women, this event will help to reduce the number of back pain complaints in the community. Health Education is a topic that is explored in both theory and practice during these events. With this program, it is hoped that pregnant women can do pregnancy exercises so that complaints of back pain and other complaints can be reduced. These are some of the desired results from this endeavor; (1). Scientific publications in journals with ISSN / Proceedings; (2). Publication in PT repocitory; (3). Leaflet; (4). Activity Video; (5). Increased knowledge